HUBUNGAN USIA IBU SAAT HAMIL DENGAN KEJADIAN STUNTING PADA BALITA DI PUSKESMAS RATAHAN KABUPATEN MINAHASA SELATAN - Junita IIolu, Selfia Mika; Purwati, Anik (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Background: Stuntingl is al chronic nutritionall problem inl toddlers which is characterizedl by shorterl height comparedl to childrenl their lage. Severall factors thatl are thought tol be thel cause ofl stunting arel the lmother's pregnancyl history whichl includes thel mother's body posturel (lshort), pregnanciesl that are tool close together, too many lbirths, thel mother's agel when pregnantl is tool old, thel mother's agel when pregnantl is tool young (underl 20 lyears). , Lilal is lessl at riskl of givingl birth tol a babyl with LBW, asl well asl inadequate nutritionall intake duringl pregnancy. Objective: Thel research objectivel of thisl study isl to find out inl general thel relationship betweenl maternal agel during pregnancyl and thel incidence ofl stunting inl toddlers aged 1-5 years at the Ratahan Community Health Center, South Minahasa Regency. Method: Analytical research usingl a crossl sectional ldesign. Thel sampling techniquel in thisl research usedl systematic random samplingl technique. The independent variable studied was the mother's age duringl pregnancy andl the dependentl variable was thel incidence ofl stunting. Data collection uses primary data using a checklist sheet including data on the child's height/length, child's weight, mother's age during pregnancy. Data analysis used univariatel and bivariatel with thel chi squarel test. lResults: Statisticall tests showedl that therel was al relationship betweenl maternal agel during pregnancyl and thel incidence ofl stunting atl the Ratahanl Communityl Health lCenter, South Minahasa Regency (lp-valuel 0.049). Age was grouped into risk agel <20l and >35l years andl non-risk/ideal lage, namely 20-35 years). Conclusion: In this study, thel results showedl that therel was al relationship betweenl maternal agel during pregnancy andl the incidencel of lstunting. Thel majority ofl mothers inl the at-risk groupl have stunted children and thel majority ofl mothers inl the no-risk groupl have non-stunting children.